The Correlation Stress Level Toward Quality of Life in Elderly People with Hypertension - Witriyani, Witriyani (Sahabat Publikasi Kuu, 2023)
Background: Elderly people is someone who due to age experiences biological, physical and behavioral changes. These changes will have an impact on all aspects of life, including health. The changes that occur can have a social and economic impact. It is very important to emphasize the quality of life in the elderly. A good quality of life for the elderly will encourage the elderly to become more independent, healthy, productive and prosperous. According to WHO, the quality of life domain for the elderly consists of four domains, including physical health, psychological health, social relationships and the environment. Hypertension is a disease that most elderly suffer from, the majority experience stress, both physical stress and psychological stress, such as getting tired easily when carrying out daily activities, difficulty sleeping, disturbed sleep and headaches. Purpose: To determine the relationship between stress levels and the quality of life of elderly people with hypertension. Method: This type of research is descriptive correlative with a cross sectional approach. The sampling technique used total sampling with a total of 42 respondents. Data collection tools used the DASS 42 and WHOQOL-BREF questionnaires, statistical tests used the Chi Square test. Results: Most respondents had moderate levels of stress, 13 respondents (31.0%) and low quality of life, 24 respondents (57.1%). The results of the bivariate test using Chi Square obtained a p-value of 0.002 (p<0.05). Conclusion: There is a relationship between stress levels and the quality of life of elderly people with hypertension